Discursos (2010)
Discuros de apertura de los certámenes de 1970, por: Benigno Guarnizo C.; M. Maitin López ; Alejandro Vásquez U.; F. L. Angulo; Julio D. Mallarino; R. Mac-Dowall; Leopoldo Angulo; E. Fajardo; y Enrique Morales